Attitude and Knowledge Towards Fruits and Vegetables Consumption Among Adults in Malaysia - Siti Hasma Hajar Mat Zin; Balkiah Moktar; Siti Haslini Zakaria (Advances in Humanities and Contemporary Studies, 2023)
Intake of fruits and vegetables is important for human health because these foods are primary sources of essential nutrients such as fibre, minerals, and vitamins. The presence of many vitamins and other substances in fruits and vegetables provides nutrients to the human body that can prevent major diseases such as noncommunicable diseases (NCDs), including certain types of cancer. However, the majority of Malaysian adults were unconcerned about the importance of fruit and vegetable consumption to their health. A global challenge is adults’ low intake of fruits and vegetables. Therefore, this study is conducted to assess the attitude and knowledge of Malaysian adults toward fruit and vegetable intake. A cross-sectional study was conducted among adults in Malaysia using an online questionnaire. A total of 291 adults were randomly chosen to participate in this study. Based on the attitude findings, more than 40% of the respondents ‘strongly agree’ that they want to consume more vegetables and enjoy eating fruits. Furthermore, more than 40% of respondents "disagree" that eating vegetables can lead to less energy. Knowledge was assessed in the areas of nutrition, protection, and general knowledge. Half of the respondents demonstrated a lack of knowledge about nutrients and protection, including general knowledge. On the mean score of nutrition knowledge of respondents toward fruit and vegetable consumption, there is a significant difference between age groups, with the difference being obvious between the age groups of less than 30 and 30 to 49 years old, as well as 50 and above. Thus, more effort is needed from the government to educate Malaysians on improving and increasing their fruit and vegetable intake. These education programs must consider the trade-off required for families to purchase more fruits and vegetables and consume the recommended number of servings per day.